Pengaruh Konsentrasi Perendaman Pandan (Pandanus amarilifolius Roxb.) sebagai Pereduksi Alami Kadar Formalin Pada Ikan Asin Teri Nasi - Amelia Handayani Burhan (Politeknik Kesehatan Bhakti Setya Indonesia, 2020)
Anchovy salted fish is a food that is in demand by the people of Indonesia. Several studies have shown that anchovy salted fish circulating in Yogyakarta traditional markets contain positive samples of salted fish containing formalin. Formalin can cause cancer and even death. Therefore, it is necessary to make efforts to reduce formalin levels, one of which is by soaking anchovy salted fish in pandan juice solution, because pandan contains saponin compounds that are able to reduce formalin levels. This study aims to determine the effect of variations in the concentration of pandan juice solution on reducing formalin levels in anchovy salted fish. The research was conducted at the Chemical Laboratory of the Bhakti Setya Indonesia Health Polytechnic, Yogyakarta. The sample used was 25 samples of anchovy salted fish obtained from 5 traditional markets in Yogyakarta. The study was conducted on samples that were positive for formalin, the determination of formalin levels was tested quantitatively by the Acidimetric Titration method using a standard solution of 0.00009 N HCl and methyl red indicator. The determination of the concentration was carried out before and after soaking the pandan juice solution for 1 hour with variations in the concentration of pandan juice soaking 25, 40, 55, 70, and 85% as much as 20 ml with a weight of 6 grams of anchovy salted fish. The results showed that of the 25 samples of anchovy salted fish there were 24 samples that were positive for formalin. The level of formalin in anchovy salted fish before treatment was 1.283% and after treatment had the following results: 1.218; 1.142; 1.025; 0.908; and 0.767% w/w. The results of statistical analysis One Way ANOVA obtained a significance value of 0.00 < 0.05, which means that variations in the concentration of pandan juice immersion have an effect on reducing formalin levels in anchovy salted fish. The optimal concentration of pandan juice immersion (Pandanus amarylifolius Roxb.) to reduce formalin levels is 85% with a decrease in levels of 40.243%